Suicide and deliberate self-harm among women in Nepal: a scoping review - Sarina Pradhan Kasaju; Anja Krumeich; Marc Van der Putten (BMC, 2021)
Abstract Background Suicide is a growing public health problem globally. Suicide accounts for 70% of violent deaths among women in low and middle income countries. In Nepal suicide is the single leading cause of death among women of reproductive age. The aim of this scoping review is to explore and understand the various contexts related to vulnerability of Nepalese woman towards suicide and deliberate self-harm. Methods A scoping review based on Arksey and O'Malley's methodological framework including a combination of peer-reviewed publications and grey literature was conducted. The National Library of Medicine's PubMed and Google Scholar search engines were used during July 2019 applying a Boolean search strategy. Results Suicide incidence was found to be higher among younger age group and married women, with poisoning as the most common means of suicide. Psychosocial and economic factors such as abuse, interpersonal conflicts, marital disputes, relationship problems, adjustment problems, unpaid loans and financial losses; and mental health conditions such as mood disorder, adjustment disorder and substance abuse disorder were found to be contributing factors for suicide and deliberate self-harm among women in Nepal. Conclusion Socio-cultural and economic factors shape family and marital relationships which impacts psycho-social and mental wellbeing of women in Nepal inciting suicidal attempts and deliberate self-harm. However, very few studies were found that explore the context of poverty, social exclusion, gender inequality, education, traditional/cultural and patriarchal system in which suicide among women in Nepal occurs.